ANALISIS PENDAPAT YUSUF QARDHAWI MENGENAI ZAKAT KEKAYAAN INVESTASI - Muhammad Ichsan, Erna Dewi (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2021)
Investment zakat is a zakat which is the result of wealth exploitation for which is obligatory on the material, this is not because it is traded, but because it is experiencing growth that provides results and business fields to its owners, by renting the material or selling the production. Because investment at this time can bring profits, and can be categorized as assets that grow and develop, So, it is obligatory to pay zakat.Yusuf Qardhawi sets the level of investment zakat to equate it with agricultural zakat, because the results of agricultural land obtained by the owner are no different from the profits of factories, buildings and others. With the determination of the zakat rate of 5% or 10% according to the results of the business and the costs spent.This study uses library research methods, by taking some data from the Qur'an, al-Sunnah and several books of fiqh and other books that have to do with these problems. The technique of extracting subject is by processing, studying books and that are related to the subject matter. The subject collected is then analyzed using descriptive analysis method, is the describe and explain several opinions covering problems related to trying to find the relationship between legal theory and reality.